Lessons learnt from CCAFS - 10 years scaling climate-smart agriculture: Insights from the review of CCAFS scaling activities, 2019 - Koerner, Jana; Dinesh, Dhanush; Loboguerrero Rodriguez, Ana María; Campbell, Bruce M. (2020)
This Info Note is based on the insights of the CCAFS core team, lessons shared by project leaders via the MARLO, and interviewees from the following CGIAR centers and partners: Bioversity, CIAT, CIMMYT, CIP, ICARDA, ICRAF, ICRISAT, IFPRI, IITA, ILRI, IRRI, IWMI, WorldFish, and WUR. After ten years’ implementation, lessons learnt of practitioners validate two concepts that CCAFS has used and developed for scaling CSA: the Three-Thirds Principle for effective science-policy engagement (Dinesh et al. 2018) applies widely for scaling CSA, when adding the element of iterative learning; and the LearningWheel with 11 cornerstones for effective research and development to improve livelihoods and the environment (Campbell et al. 2006) is a useful framework for managing not only R4D, but also scaling processes.